The Effectiveness Of The Implementation Of The Government Agency Performance Accountability System (Sakip) In The East Java Provincial Government - Dewi Nurkholilah; Fedianty Augustinah; Ulul Albab; Sri Kamariyah; Himad Ali (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The Performance Accountability System (SAKIP) is a crucial framework for improving the efficiency and effectiveness of government institutions in Indonesia. Within the East Java Provincial Government, SAKIP aims to enhance transparency, accountability, and performance measurement. However, effective implementation requires not only strong organizational commitment but also the ability to adapt to changing environments and optimize human resources. This study used a qualitative approach, including document analysis, interviews, and field observations, to assess SAKIP implementation in East Java. Key informants included government officials involved in performance management and strategic planning. The research also evaluated the impact of training programs like workshops and technical guidance (Bimtek) on improving employee understanding of SAKIP. Findings indicate that, despite adequate office equipment, the integration of SAKIP-related applications remains a major challenge. Limited human resource capabilities further hinder the effectiveness of the system, affecting data management and performance evaluation processes. While the East Java Provincial Government has demonstrated commitment to improving performance, these limitations continue to restrict the full potential of SAKIP. The study highlights the need for better infrastructure, continuous training, and enhanced technical skills to fully realize SAKIP's benefits. It also emphasizes the importance of aligning human resource development with organizational goals to create a more adaptive and efficient public sector. The paper concludes with recommendations for addressing these challenges, including improved planning, measurement, and the integration of digital solutions to support long-term performance improvement.